2017
DOI: 10.2177/jsci.40.68
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for personalized combination immunotherapy for solid tumors based on adoptive cell therapies and immune checkpoint blockade therapies

Abstract: summaryImmune checkpoint blockade (ICB) and adoptive cell therapies (ACT) with antigen-receptor gene-engineered T cells have been shown to be successful for a limited number of patients with solid tumors. Responders to ICB therapy typically have T cell-inflamed tumors. Thus, it is important to develop strategies that convert non-T cell-inflamed tumors to T cell-inflamed tumors. Although chimeric antigen receptor transduced T (CAR-T) cell therapy targeting hematological malignancies demonstrated durable clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Furthermore, the local adaptive immune-suppression should be noted. 29 Previous studies showed the abundance of Tregs 5,10,41 and M2 shows a gradual increase in F I G U R E 3 Immune evasion before tumor invasion in early cervical squamous carcinogenesis. (A) Spearman's correlation between absolute score and immunoinhibitive genes expression across the progression of normal to advanced stages.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the local adaptive immune-suppression should be noted. 29 Previous studies showed the abundance of Tregs 5,10,41 and M2 shows a gradual increase in F I G U R E 3 Immune evasion before tumor invasion in early cervical squamous carcinogenesis. (A) Spearman's correlation between absolute score and immunoinhibitive genes expression across the progression of normal to advanced stages.…”
Section: Discussionmentioning
confidence: 98%
“…Two types of immunosuppression mechanism exist in the TME-a tumor-intrinsic and a local adaptive immune-suppression. 29 In SCC, the P53 inactivation may cause by the increased oncogenic human papillomavirus (HPV) protein E6 the binding with tumor suppressor protein (p53), 30 resulting in uncontrolled cellular proliferation, DNA damage, and chromosomal instability. 31 A dramatic decrease in estrogen receptor α expression throughout cervical cancer progression, 9 as well as the down-enriched early and late estrogen response discovered in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The good results were observed in clinics with CAR-T cells therapy in hematological malignancies, however, it is still a change in the solid tumors because of antigen loss in tumor cells, the lack of unique antigens and the immune-suppressive tumor microenvironment of solid tumors [50, 51]. So in order to improve the effect of CAR-T cells therapy, many progresses have been made by incorporating CARs with another effector molecules such as PD1 switch receptors, anti-oxidant enzymes, matrix degradation enzymes and so on [5256].…”
Section: Challenges For Car-t Cell Therapymentioning
confidence: 99%
“…CAR-T cell therapy has demonstrated remarkable success in hematologic malignancies and FDA has approved the first CAR-T product in the treatment of acute lymphoid leukemia (ALL). Despite favorable responses of CAR-T in patients with non-solid malignancies, the outcome in solid tumor is far from satisfactory partly owing to the lack of unique antigens, antigen loss in cancer cells, the suppressive tumor microenvironment and modified T cells are rarely accumulating in tumors (85,86). Many investigations are ongoing on converting this gloomy option in solid tumor.…”
Section: Perspectivesmentioning
confidence: 99%